SHOOL OF NURSING COMPETENCY-BASED CURRICULUM - Jara Concha, Patricia; Stiepovic Bertoni, Jasna (Investigación y Educación en Enfermería, 2008)
<!–[if gte mso 9]> <![endif]–><!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> We analyze the impact of higher education on the society and its ﬁtting within a globalized world and discuss some notions regarding nursing education particularly at the graduate level in the current context driven by the education-production paradigm. We present a critical analysis of the components of a competence-based curriculum for a master of nursing program and discuss its implications for both work and academic contexts. Finally, we propose three basic competences for nursing graduate education based on three key dimensions of knowing: including to know, to know how and to know being.